Long‐term survival of young endometrial cancer patients desiring fertility preservation treated with hysteroscopic resection followed by hormone therapy (NEMO technique). Issue 2 (17th June 2020) - Mazzon, Ivan; Masciullo, Valeria; Scambia, Giovanni; Ferrandina, Gabriella; Corrado, Giacomo
Abstract : The NEMO technique is a therapeutic option for women with Stage IA endometrial cancer who wish to preserve fertility.